Delineating the Potential Therapeutic Effects of Lobaric Acid as a Novel Strategy in the Treatment of Melanoma - Jama, Huda Abdirizak; Ensoy, Mine; Yılmazer, Açelya; Cansaran-Duman, Demet (Current Medicinal Chemistry, 2025)
IntroductionMelanoma is one of the most dangerous and common types of cancer in humans. In order to minimize the toxicity and side effects of melanoma treatment, it is important to identify drug candidates that have strong anti-cancer activity and fewer side effects. Lobaric acid is a small molecule that has been found to have significant anti-cancer effects on various types of cancer cells.MethodsThe study aimed to investigate the effects of lobaric acid on human melanoma cell lines (A-375, MDA-MB-435, G-361, and WM-115) and normal human epidermal melanocyte cells. The study also examined the regulation of cell cycle and apoptosis, as well as the gene expression level of apoptosis-related genes and regulatory proteins to induce apoptosis in melanoma cells.ResultsThe study suggests that lobaric acid may have an effect on the proliferation of A-375 melanoma cells, with results indicating a dose- and time-dependent manner. Additionally, the study found that the expression levels of 70 target genes out of 88 apoptosis-related genes in the primary apoptosis library panel were obtained. Out of these, 54 genes showed an increase in expression levels, while 16 genes showed a decrease. Moreover, it has been determined that the levels of apoptosis-related proteins, such as Casp3, Casp7, Casp9, and PARP, were increased. The results suggest that lobaric acid induces apoptosis through the extrinsic pathway by upregulating the expression of Caspases and PARP.ConclusionThe findings of this study provided a strong basis for the use of lobaric acid as a potential therapeutic agent in the treatment of melanoma.
Keywords: small molecule